Expression of TMEM16A in Colorectal Cancer and Its Correlation With Clinical and Pathological Parameters - Li, Hongxia; Yang, Qiwei; Huo, Sibo; Du, Zhenwu; Wu, Fei; Zhao, Haiyue; Chen, Shifan; Yang, Longfei; Ma, Zhiming; Sui, Yujie (Frontiers in Oncology, 2021)
TMEM16A is a recently identified calcium-activated chloride channel (CaCC) and its overexpression contributes to tumorigenesis and progression in several human malignancies. However, little is known about expression of TMEM16A and its clinical significance in colorectal cancer (CRC). TMEM16A mRNA expression was determined by quantitative real time-PCR (qRT-PCR) in 67 CRC tissues and 24 para-carcinoma tissues. TMEM16A protein expression was performed by immunohistochemistry in 80 CRC tissues. The correlation between TMEM16A expression and clinicopathological parameters, and known genes and proteins involved in CRC was analyzed. The results showed that TMEM16A mRNA expression was frequently detected in 51 CRC tissues (76%), whereas TMEM16A protein expression was determined at a relatively lower frequency (26%). TMEM16A mRNA expression in tumor tissues was higher than its expression in normal para-carcinoma tissues (P < 0.05). TMEM16A mRNA expression was significantly correlated with TNM stage (p = 0.039) and status of lymph node metastasis (p = 0.047). In addition, there was a strong positive correlation between TMEM16A mRNA expression and MSH2 protein. More importantly, TMEM16A protein expression was positively associated with KRAS mutation, and negatively correlated with mutant p53 protein. Logistic regression analysis demonstrated that TMEM16A mRNA expression was an important independent predictive factor of lymph node metastasis (OR = 16.38，CI: 1.91-140.27，p = 0.01). TMEM16A mRNA and protein expression was not significantly related with patient survival. Our findings provide original evidence demonstrating TMEM16A mRNA expression can be a novel predictive marker of lymph node metastasis and TMEM16A protein expression may be an important regulator of tumor proliferation and metastasis in CRC.